Hardware implementation of smart home automation system using Aurdino UNO. - Kunaraj, A.; Joy Mathavan, J.; Mathushan, M.; Kamalesan, G.M. (Springer, Singapore, 2020)
Home automation system is one of the developing systems nowadays. This project is concentrating on automatically controlling the home by monitoring the devices or appliances working at home. Arduino technology is used as the control system. This system enhances comfort, safety and economical usage. According to this idea, the system designed to manage power consumption at economical level and make the living style easier. Bluetooth peering between client and server act as a wireless communication system. In this work, mobile station is the client and HC6 Bluetooth module is the server which is connected directly with Arduino Uno.
Keywords: Arduino UNO; Home automation; Temperature sensor